Analysis of light load losses in soft-switched full-bridge (ZVS) converter - Biscocho, Ferdinand (2005)
To meet the demand for power supply with higher power density and higher efficiency, the converter is pushed to operate at higher frequencies to reduce component sizes. And to keep the losses at minimum, soft-switching techniques are employed. But soft-switching can only be optimized at certain load conditions, thus losses may increase significantly at light loads where soft-switching is lost. When using ISL6551 control scheme to realize soft-switched (ZVS) full bridge converter, an imbalance in the zero voltage transitions happens at the lower FET. A method to overcome this problem is presented. Complexity versus improved light load efficiency for optimized ZVS Full-Bridge is also presented.